Khalwat as a moral crime in Malaysia: issues and realities - Wan Muhammad, Ramizah (Bangladesh Islamic Law Research and Legal Aid Centre, 2015)
Khalwat is considered a moral crime in Malaysian Islamic law. It is one of the syariah criminal offences under the category of offences relating to decency in statutory provisions in states enactments and Federal Territories act. There are a few important issues to be discussed in this paper. Other than on the concept of khalwat in Islamic criminal law and the meanings of khalwat in Malaysian Islamic law and the punishments, this paper will look at the issue at the extent of truth of “criminalizing’ khalwat in the context of Islamic criminal law. Other the conceptual issues in hukum shara’, there are other practical and real ssues that arise in Malaysia such as the involvement of a non Muslim in khalwat cases, the punishment provided which are too lenient and the procedure how the Department of Religious Affairs enforce the laws.. At the same time, a new perspective can be looked at to minimize the current issues problems and highlight the positive sides of a current law if any.